2008
DOI: 10.1373/clinchem.2007.098780
|View full text |Cite
|
Sign up to set email alerts
|

Haptoglobin Polymorphism: A Novel Genetic Risk Factor for Celiac Disease Development and Its Clinical Manifestations

Abstract: Background: Haptoglobin (Hp) α-chain alleles 1 and 2 account for 3 phenotypes that may influence the course of inflammatory diseases via biologically important differences in their antioxidant, scavenging, and immunomodulatory properties. Hp1-1 genotype results in the production of small dimeric, Hp2-1 linear, and Hp2-2 cyclic polymeric haptoglobin molecules. We investigated the haptoglobin polymorphism in patients with celiac disease and its possible association to the presenting symptoms. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…The authors found that the phenotype HP2-1 was associated with a significant risk of CD. Conversely, HP2-2 was less frequent in CD patients than in controls, but patients having this phenotype were at an increased risk for severe malabsorption (127). Therefore, it is tempting to hypothesize that one copy of the zonulin gene increases the risk of CD because of its permeating effect on the intestinal barrier, while two copies of this gene, causing a severe malabsorption secondary to a more profound intestinal barrier dysfunction, led to high mortality and, therefore, was negatively selected during evolution.…”
Section: H Zonulin Is Upregulated In the Intestinal Mucosa Of Celiacmentioning
confidence: 89%
See 1 more Smart Citation
“…The authors found that the phenotype HP2-1 was associated with a significant risk of CD. Conversely, HP2-2 was less frequent in CD patients than in controls, but patients having this phenotype were at an increased risk for severe malabsorption (127). Therefore, it is tempting to hypothesize that one copy of the zonulin gene increases the risk of CD because of its permeating effect on the intestinal barrier, while two copies of this gene, causing a severe malabsorption secondary to a more profound intestinal barrier dysfunction, led to high mortality and, therefore, was negatively selected during evolution.…”
Section: H Zonulin Is Upregulated In the Intestinal Mucosa Of Celiacmentioning
confidence: 89%
“…10). Interestingly, Papp et al (127) have recently reported that HP polymorphism represents a novel genetic risk factor for CD development and its clinical manifestations. The authors found that the phenotype HP2-1 was associated with a significant risk of CD.…”
Section: H Zonulin Is Upregulated In the Intestinal Mucosa Of Celiacmentioning
confidence: 99%
“…The enhanced expression of zonulin correlated with disease activity, because CD patients who were on a GFD showed mean values for zonulin expression that were intermediate to those of patients with active CD and normal controls. Interestingly, Papp et al (35) recently reported that a polymorphism in the HP gene represents a previously undescribed genetic risk factor for CD development and its clinical manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…Zonulin is a prehaptoglobin (HP) 2 [4], a molecule that, to date, has been regarded as only the inactive precursor for HP2, 1 of the 2 genetic variants (together with HP1) of human HPs. Several studies have suggested that the presence of the HP2 allele correlates with higher risk of developing immune-mediated diseases [13] and that HP2 homozygosis is associated with poor prognosis [13] and decreased longevity [14]. The only function assigned to HPs to date has been to bind hemoglobin to form stable complexes and thereby prevent hemoglobin-induced oxidative tissue damage [15].…”
Section: Discussionmentioning
confidence: 99%